1998
DOI: 10.1016/s0896-6273(00)80592-9
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Rivalry and Visual Awareness in Human Extrastriate Cortex

Abstract: We used functional magnetic resonance imaging (fMRI) to monitor stimulus-selective responses of the human fusiform face area (FFA) and parahippocampal place area (PPA) during binocular rivalry in which a face and a house stimulus were presented to different eyes. Though retinal stimulation remained constant, subjects perceived changes from house to face that were accompanied by increasing FFA and decreasing PPA activity; perceived changes from face to house led to the opposite pattern of responses. These respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
492
3
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 753 publications
(548 citation statements)
references
References 15 publications
48
492
3
5
Order By: Relevance
“…These studies have found that activity during rivalry corresponds to activity during physical alternations of stimuli over a large posterior portion of the brain ranging from temporal (fusiform and parahippocampal) areas (Tong, Nakayama, Vaughan, & Kanwisher, 1998), over V1 (Lee & Blake, 2002;Polonsky, Blake, Braun, & Heeger, 2000), including monocular areas such as the blind spot representation (Tong & Engel, 2001) and extending all the way to the lateral geniculate nucleus (Haynes, Deichmann, & Rees, 2005;Wunderlich, Schneider, & Kastner, 2005). Thus, in these areas of the brain, fMRI activity during dominance is comparable to activity during monocular viewing and activity during suppression is comparable to when the stimulus is not presented to the subject.…”
Section: Accounting For Conflicting Neurophysiological and Imaging Evmentioning
confidence: 99%
“…These studies have found that activity during rivalry corresponds to activity during physical alternations of stimuli over a large posterior portion of the brain ranging from temporal (fusiform and parahippocampal) areas (Tong, Nakayama, Vaughan, & Kanwisher, 1998), over V1 (Lee & Blake, 2002;Polonsky, Blake, Braun, & Heeger, 2000), including monocular areas such as the blind spot representation (Tong & Engel, 2001) and extending all the way to the lateral geniculate nucleus (Haynes, Deichmann, & Rees, 2005;Wunderlich, Schneider, & Kastner, 2005). Thus, in these areas of the brain, fMRI activity during dominance is comparable to activity during monocular viewing and activity during suppression is comparable to when the stimulus is not presented to the subject.…”
Section: Accounting For Conflicting Neurophysiological and Imaging Evmentioning
confidence: 99%
“…For example, if two different objects or images are presented to the two eyes, either they are merged into one, if coherent enough (binocular fusion) [408], or only one of them will be seen at any one time (binocular rivalry) [409]. The same ever-present temporal integration span is responsible for the binding of different features (color, texture, luminance and so on) of the same object (feature binding) 56 and for the binding of several distinct parts of complex objects or scenes (part binding) 57 together [412].…”
Section: Phenomenal Timementioning
confidence: 99%
“…Second, neuroimaging methods have revealedspecific face-selective regions in the fusiform gyrus, namely the ''FFA'' [7]. Third, FFA responses to vaguely face-like stimuli correlate with the subjective experience of face perception [8,[136][137][138], suggesting that the FFA responds to the face gestalt. Fourth, FFA responses are modulated by changes in facial features and configuration [139].…”
Section: Neural Substrates Of Identity Recognition In Healthy Adults:mentioning
confidence: 99%